A biophysiological perspective on enhanced nitrate removal from decentralized domestic sewage using gravitational-flow multi-soil-layering systems. (February 2020) - Song, Pei; Huang, Guohe; Hong, Yongyuan; An, Chunjiang; Xin, Xiaying; Zhang, Peng
Abstract: Multi-soil-layering (MSL) system with brick-wall pattern structure and gravitational flow can be used for decentralized rural domestic sewage treatment. The capability of soil for contaminant removal is maximized within soil mixture blocks (SMBs). However, the performance of removing nitrate was still not ideal during operation. To improve its performance in MSL system, the relationship between biophysiological characteristics of denitrifying species and operating conditions was studied. Microbial species diversity of activated sludge and soil samples were analyzed. The significant effects of independent factors and their interactions on microbial species diversity and denitrifying species abundance were revealed on the basis of factorial analysis. The results indicated activated sludge in SMBs played a key role in increasing the richness of denitrifying species in MSL system. Slow-release poly (butylene succinate) (PBS) had the most dominant positive effect on increasing denitrifying species abundance. Submersion had significantly positive effect on species richness in SMBs. These three factors, including activated sludge, PBS in SMBs, and submersion condition had different significant effects on microbial responses. They were favorable for denitrification and ensuring a better removal efficiency of nitrate and total nitrogen. The porous zeolites were served as the habitats for most of aerobic bacteria to form biofilms, which could promote the oxygen consumption in both sewage and system to improve denitrification in SMBs. The results could help on the enhancement of denitrification in MSL system from biophysiological insights. It can provide a sound strategy for using MSL system with great performance on contaminant removal. Graphical abstract: Image 1 Highlights: Investigated microbial diversity in soil mixture blocks through gene sequencing. Revealed biophysiological nature of nitrate removal in multi-soil-layering systems. Analyzed the interactive effects of operating factors on denitrifying species. Explored relationship between biophysiological characteristics and denitrification.